1988
DOI: 10.1128/aem.54.5.1079-1084.1988
|View full text |Cite
|
Sign up to set email alerts
|

Use of phylogenetically based hybridization probes for studies of ruminal microbial ecology

Abstract: To address the long-standing need for more precise descriptions of natural microbial ecosystems, 16S rRNAs were used to track certain species and phylogenetically coherent groups of microorganisms in their natural setting without culturing. Speciesand group-specific 16S rRNA-targeted oligonucleotide hybridization probes were developed to enumerate various strains of Bacteroides succinogenes and Lachnospira multiparus-like organisms in the bovine rumen before, during, and after perturbation of that ecosystem by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
385
0
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 713 publications
(395 citation statements)
references
References 26 publications
3
385
0
3
Order By: Relevance
“…However, PCR detections of Fibrobacter and its relatives tend to underestimate the actual abundance of this group, possibly due to low accessibility of the rRNA primer binding sites (Tajima et al, 2001;Firkins and Yu, 2006). The specificity of the chosen forward primer to detect Fibrobacter has already been demonstrated before (Stahl et al, 1988) and was confirmed by our own in silico analyses (data not shown). However, sequencing of bands from SSCP profiles targeting Fibrobacter revealed the Table 4.…”
Section: Discussionsupporting
confidence: 83%
“…However, PCR detections of Fibrobacter and its relatives tend to underestimate the actual abundance of this group, possibly due to low accessibility of the rRNA primer binding sites (Tajima et al, 2001;Firkins and Yu, 2006). The specificity of the chosen forward primer to detect Fibrobacter has already been demonstrated before (Stahl et al, 1988) and was confirmed by our own in silico analyses (data not shown). However, sequencing of bands from SSCP profiles targeting Fibrobacter revealed the Table 4.…”
Section: Discussionsupporting
confidence: 83%
“…RNA was quantitatively extracted from approximately 0.6 g of wet sediment using the bead-beating disruption mentioned previously (Stahl et al, 1988). RNA concentration was determined spectrophotometrically, as described above.…”
Section: Cloning and Dna Sequencingmentioning
confidence: 99%
“…The RNA isolated from pure cultures [Ketogulonogenium vulgare DSM 4025, Nitrosomonas europaea ATCC 25978, Cytophaga johnsonae ATCC 17061, Arthrobacter globiformis ATCC 8010, Verrucomicrobium spinosum ATCC 43997, Planctomyces limnophilus ATCC 43296, Acidobacterium capsulatum ATCC 51196 and Saccharomyces cerevisiae American Ale Yeast 1056 (Wyeast Laboratories, INCS)] were included on all membranes as standards to control for differences in the specific activity of labelled probes and to account for the possibility of non-specific probe binding. Hybridization protocols for [ 32 P]-5¢-labelled oligonucleotide probes were previously described in detail (Stahl et al, 1988). Radiolabelled oligonucleotide probes that bind to the rRNA molecules from specific microbial groups were then used to determine the relative abundance of microbial group rRNA.…”
Section: Site Description and Soil Samplingmentioning
confidence: 99%
“…Within a soil sample, the relative abundance of rRNA derived from a specific group was measured as the ratio of the signal derived from a group-specific probe to the signal derived from the universal probe. This approach for determining microbial rRNA abundance has been used previously to describe aspects of microbial community structure (Stahl et al, 1988). Relating specific probe binding to universal probe binding controls for variability in the total amount of RNA recovered from each soil sample, and also controls for the presence of hybridization inhibitors that may co-purify with RNA from soil.…”
Section: Determination Of Rrna Abundancementioning
confidence: 99%